OccupationalHearing NImpairmentoise-induced Hearing Loss and Hypertension Associated with Long Term Occupational Exposure to Noise - A. Rajaei-Fard; M. Madahi; M. Neghab (Salāmat-i kār-i Īrān, 2008)
Background and aims   Noise induced hearing loss is a permanent,usually, bilateral hearing  impairment due to long term exposure to high levels of noise and exposure of workers to noise  represents one of the most common occupational hazards. Although noise has also been suggested  to increase the prevalence of hypertension, evidence for this association is not conclusive. This historical cohort study was undertaken to evaluate the auditory effects of noise and to further examine the hypothesis that a link between noise exposure and hypertension exists.   Methods   The study population consisted of 140 healthy male employees from a local petrochemical industry with history of past and present exposure to noise and 140 matched healthy male unexposed individuals from the same industry (referent group). Aquestionnaire with 40 questions concerning age, sex, weight, height, length of employment, workplace noise  level and history of hypertension was administered. Furthermore, subjects were physically examined, their blood pressure were taken under normal resting position and underwent audiometry testing. Similarly, sound pressure level and octave band analyzing in different stations  of workplace carried out for every employee, and then Leq calculated. Data were analyzed by  SPSS 13, using student's t test and Chi-square.   Results   The prevalence of hearing impairment in this study was 38.5 percent among exposed  and 7.8 percent among unexposed group and the difference was statistically significant  (p<0.0001). Similarly, the prevalence of hypertension in exposed group was significantly higher  than that of unexposed group.   Conclusion   These findings while provide corroborative evidence to further substantiate the  notion that exposure to noise is associated with hearing impairment, they also support the  proposition that long term occupational exposure to noise appears to be a risk factor for arterial hypertension